The legend of the Baal-Shem - Buber, Martin, 1878-1965 (Mythos (Princeton, N.J.), 1995)
The Jewish philosopher Martin Buber spoke directly to the most profound human concerns in all his works, including his discussions of Hasidism, a mystical-religious movement founded in Eastern Europe by Israel ben Eliezer, called the Baal-Shem (the Master of God's Name). Living in the first part of the eighteenth century in Podolia and Wolhynia, the Baal-Shem braved scorn and rejection from the rabbinical establishment and attracted followers from among the common people, the poor, and the mystically inclined. Here Buber offers a sensitive and intuitive account of Hasidism, followed by twenty stories about the life of the Baal-Shem. This book is the earliest and one of the most delightful of Buber's seven volumes on Hasidism and can be read not only as a collection of myth but as a key to understanding the central theme of Buber's thought: the I-Thou, or dialogical, relationship.